Relation Between The Awarenees of Culinary Msme Actors and Trademark Protection - Lidia Kando Br Gea; Hari Sutra Disemadi (Universitas Islam Balitar, Blitar, 2022)
MSME is business owned by individuals or business entities in which business actors produce their own products. These products need legal protection although there are still many MSME actors who have not registered their trademarks. According to the data, the number of MSME actors who have registered their trademark to Indonesian Directorate General of Intellectual Property (in Indonesia says DJKI) are still low, whereas a trademark is an immaterial wealth or economic asset for business actors. In addition, unregistered trademarks are also vulnerable to abuse by other parties. This will result in losses for the business actors themselves. Therefore, the trademark needs to be registered in DJKI in order to get legal protection. Based on these problems, this research uses non-doctrinal research methods to examine the regulation of trademark protection for MSME businesses in Indonesia and examine the relationship between the awareness of culinary MSME actors in Batam City and trademark protection. This research indicates that the regulation of trademark protection in Indonesia is contained in the Trademark & Geographical Indications Law. It was also found that there are still MSME actors who do not aware about the legal protection for their intellectual works so they had not registered them. For this reason, the government and all parties are expected to provide literacy on the importance of trademark protection. This will minimize the occurrence of intellectual property infringement and disputes. In addition, the existence of intellectual property protection in Indonesia provides a sense of security and legal certainty for trademark owners.